Advanced Engineering Ceramics and Composites : Selected, peer reviewed papers of the 4th International Symposium on Advanced Ceramics, Osaka International Convention Center, November 14-18, 2010, Japan - Goto, Takashi; Cheng, Yi-Bing; Akatsu, Takashi (Key engineering materials ;, 2011)
The cutting edge of engineering ceramic research is evolving rapidly, leading into new fields far beyond the conventional image of ceramics. Careful tailoring of micro- and nano-structures, in particular, is yielding superior mechanical and chemical properties, such as high hardness, high strength, good heat/corrosion resistance and good tribological properties. This special collection comprises papers from researchers working in the fields of ceramics and composites and thus provides an opportunity for the cross-pollination of knowledge and experience in interdisciplinary fields of materials science and engineering. Intensive discussions were held on the topics of silicon carbide and composites, nitride ceramics, the mechanical properties of ceramics, the sintering of ceramics, ceramics coating and the processing of functional ceramics. This work constitutes an invaluable handbook guide to a rapidly evolving subject. Review from Book News Inc.: Exploring how ceramic materials are being tailored for a number of properties and applications, researchers cover silicon carbide and composites, nitride ceramics, mechanical properties of ceramics, sintering ceramics, ceramics coating, and processing functional ceramics. Among the 41 topics are the microstructures and properties of three-phase carbon and ceramic matrix composites, the effect of heat treatment on thermal conductivity in silicon nitride ceramics, strengthening mechanisms of high-strength reaction-sintered silicon carbide, sintering silicon carbide ceramics with the co-addition of gadrinium oxide and silica and their mechanical properties, environmental barrier coatings for silicon nitride, and microelectronics package design using experimentally validated modeling and simulation. (Annotation ©2011 Book News Inc. Portland, OR).